Climate change and management of biofilms within drinking water distribution systems - Calero Preciado, C.; Soria-Carrasco, V.; Boxall, J.; Douterelo, I. (Frontiers in Environmental Science, 2022)
Climate change will increase the temperature of water in our drinking water distribution systems, impacting the biofilms that grow in these vast infrastructure systems and hence the quality and safety of drinking water at the tap. Using a full-scale laboratory-controlled facility we studied the impact of such temperature increase and the impacts of different control strategies. Our results show that increase temperature from 16 to 24°C changed the biofilm community structure and increased the potential for discolouration. Interventions of flushing only or flushing supplemented with hyperchlorination showed similar reduction in discolouration potential and reduced the abundance of microorganisms that can compromise water quality and safety such as the bacteria Flavobacterium or Sphingobium, and the fungi Fusarium and Cladosporium. However, there was no difference between the interventions, suggesting no benefit from adding hyperchlorination. This study provides useful understanding to inform strategies for managing biofilms within DWDS, understanding and mitigating the impact of increasing temperature due to climate change.